Association of the SNPs in CCL2 and CXCL12 genes with the susceptibility to breast cancer: a case-control study in China - Zhao, Duanchong; Yu, Xingxing; Huang, Hongli; Zou, Shuqing; Zhu, Pingxiu; Lin, Yuxiang; Song, Mengjie; Fu, Fangmeng; Yang, Haomin (Frontiers in Oncology, 2024)
BackgroundChemokines are well-known for playing an essential role in the development of cancer. However, the association between SNPs in the CCL2 and CXCL12 genes and the susceptibility to breast cancer remains unclear.MethodsA case-control study was conducted in southeast China, including 1855 breast cancer patients and 1838 cancer-free controls. The association between single nucleotide polymorphisms (SNPs) in the CCL2 and CXCL12 genes and the susceptibility to breast cancer was investigated using logistic regression models. The association between plasma CCL2 and CXCL12 with breast cancer was further examined in 72 patients and 75 controls.ResultsThe CXCL12 SNP rs3740085 was associated with breast cancer in the additive model (OR=1.15, 95%CI=1.01-1.32), particularly in postmenopausal women. The association between rs1024611 in CCL2 and breast cancer was only found in women with a BMI of ≥24kg/m2. SNPs in the CCL2 gene were mainly associated with PR-positive breast cancer, whereas rs1144471 in CXCL12 was associated with ER-negative (OR=0.43, 95% CI=0.23-0.84), PR-negative (OR=0.38, 95% CI=0.19-0.74), and HER-2-positive (OR=1.27, 95% CI=1.03-1.56) breast cancer. The interaction between rs1801157 and rs3740085 in CXCL12 SNPs was statistically significant, and rs3740085 was also associated with breast cancer survival. Additionally, we found a strong association between plasma CXCL12 and breast cancer.ConclusionCCL2 and CXCL12 SNPs are associated with breast cancer susceptibility in overweight and postmenopausal women, and the effect varies according to subtypes. The interaction of SNPs within CXCL12 gene and the association with breast cancer survival further suggest potential targets for improved risk assessment and treatment strategies.